The Role of Arbuscular Mycorrhizal Fungi in Enhancing Crop Resilience and Soil Health: A Review - Özgen, İnanç; Iddrısu, Abdul Mumeen (My University, 2026)
Sustainable agriculture has become a very important concept in food, feed and biofuel production. This has become so, due to increasing climate impacts as well as exponential increase in the world’s population, which triggers the need to cultivate more. One of the cornerstones of sustainable agriculture is soil health. Since their identification, Arbuscular Mycorrhizal Fungi (AMF) have been reported to play key roles in plant stress management. This review was carried out with the main aim of exploring the applications of Arbuscular Mycorrhizal Fungi in agriculture. Some recent studies were reviewed to ascertain the effects of AMF on crop performance under stress (drought, pathogens, salinity, micro-plastics) as well as the molecular processes leading to the establishment of symbiosis. This study further compared methods and results from various studies to pinpoint some key areas which need to be studied in order to bridge the information gap. The research concluded that AMF have great potential in the future of sustainable agriculture. On the other hand, it has been identified that, hosts switch to symbiosis following some level of stress. However, it is not clear the stage of stress at which hosts begin to switch to AMF association. It is therefore recommended that in-depth studies into various levels of moisture and nutrients at which symbiosis is the most beneficial should be carried out. Furthermore, other substances such as plant growth regulators and biochar should be incorporated in future research considering positive results observed in preliminary research.
Keywords: Mantar Bilimi; Bitki Bilimleri; Ziraat; Toprak Bilimi